Associated factors of job stress among employees: a case study at Wisma Ilmu, Tabung Haji, Kota Bharu, Kelantan / Nur Hanis Bukhori - Bukhori, Nur Hanis (2015)
According to the current World Health Organization's (WHO) definition, occupational or work-related stress "is the response people may have when presented with work demands and pressures that are not matched to their knowledge and abilities and which challenge their ability to cope. Job stress is one of the most important workplace health risks for employees in developed and developing countries (Paul, 2002; Danna and Griffin, 2002). The aim of this study was investigate the association factors of Job stress among employees. The independent variables were obstacle from home, organizational structure, management role, career and achievements, relationship with colleagues and workload The research instrument was a structured questionnaire. A proportionate stratified random sampling technique was used to select the respondent for this study. A total of 138 employees at Wisma Ilmu, Tabung Haji, Kota Bharu constituted the sample. The results shown that among the factors, the obstacle from home, management role, career and achievements, elationship with colleagues and workload were found to be significant predictors of Job stress contributing 84.2 per cent of Job stress. The balance 15.8 per cent was explained by the other factors. In addition, it was found that, management role the most significant factors among other variables